Solve for y (complex solution)
y=\frac{i\sqrt{2\left(\sqrt{3001}-29\right)}}{6}\approx 1.196786988i
y=-\frac{i\sqrt{2\left(\sqrt{3001}-29\right)}}{6}\approx -0-1.196786988i
y = -\frac{\sqrt{2 {(\sqrt{3001} + 29)}}}{6} \approx -2.157433966
y = \frac{\sqrt{2 {(\sqrt{3001} + 29)}}}{6} \approx 2.157433966
Solve for y
y = -\frac{\sqrt{2 {(\sqrt{3001} + 29)}}}{6} \approx -2.157433966
y = \frac{\sqrt{2 {(\sqrt{3001} + 29)}}}{6} \approx 2.157433966
Graph
Share
Copied to clipboard
9y^{4}-29y^{2}+20-80=0
Subtract 80 from both sides.
9y^{4}-29y^{2}-60=0
Subtract 80 from 20 to get -60.
9t^{2}-29t-60=0
Substitute t for y^{2}.
t=\frac{-\left(-29\right)±\sqrt{\left(-29\right)^{2}-4\times 9\left(-60\right)}}{2\times 9}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. Substitute 9 for a, -29 for b, and -60 for c in the quadratic formula.
t=\frac{29±\sqrt{3001}}{18}
Do the calculations.
t=\frac{\sqrt{3001}+29}{18} t=\frac{29-\sqrt{3001}}{18}
Solve the equation t=\frac{29±\sqrt{3001}}{18} when ± is plus and when ± is minus.
y=-\sqrt{\frac{\sqrt{3001}+29}{18}} y=\sqrt{\frac{\sqrt{3001}+29}{18}} y=-i\sqrt{-\frac{29-\sqrt{3001}}{18}} y=i\sqrt{-\frac{29-\sqrt{3001}}{18}}
Since y=t^{2}, the solutions are obtained by evaluating y=±\sqrt{t} for each t.
9y^{4}-29y^{2}+20-80=0
Subtract 80 from both sides.
9y^{4}-29y^{2}-60=0
Subtract 80 from 20 to get -60.
9t^{2}-29t-60=0
Substitute t for y^{2}.
t=\frac{-\left(-29\right)±\sqrt{\left(-29\right)^{2}-4\times 9\left(-60\right)}}{2\times 9}
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. Substitute 9 for a, -29 for b, and -60 for c in the quadratic formula.
t=\frac{29±\sqrt{3001}}{18}
Do the calculations.
t=\frac{\sqrt{3001}+29}{18} t=\frac{29-\sqrt{3001}}{18}
Solve the equation t=\frac{29±\sqrt{3001}}{18} when ± is plus and when ± is minus.
y=\frac{\sqrt{2\sqrt{3001}+58}}{6} y=-\frac{\sqrt{2\sqrt{3001}+58}}{6}
Since y=t^{2}, the solutions are obtained by evaluating y=±\sqrt{t} for positive t.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}